2004
DOI: 10.1093/carcin/bgh276
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM, INP10, P-cadherin, tPA and ITGB4 over-expression in malignant pleural mesotheliomas revealed by combined use of cDNA and tissue microarray

Abstract: Malignant pleural mesothelioma (MM) is a rare tumour with high mortality, which can exhibit various morphologies classified as epithelioid, biphasic and sarcomatoid subtypes. To investigate the molecular changes in these tumours, we studied gene expression patterns by combined use of cDNA arrays and tumour tissue microarrays (TMA). Deregulation of the expression of 588 cancer-related genes was screened in 16 MM comprising all three subtypes and compared with references, i.e. normal mesothelial cell lines and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Unexpectedly, genes encoding calretinin, vascular endothelial growth factor (VEGF) receptor and mesothelin proteins overexpressed in mesothelioma were not differentially expressed. However, recent studies showed that these are also expressed in normal mesothelial cells [103][104][105].…”
Section: Figurementioning
confidence: 99%
“…Unexpectedly, genes encoding calretinin, vascular endothelial growth factor (VEGF) receptor and mesothelin proteins overexpressed in mesothelioma were not differentially expressed. However, recent studies showed that these are also expressed in normal mesothelial cells [103][104][105].…”
Section: Figurementioning
confidence: 99%
“…We used two kind of gene expression determination, SYBRGreen I (for β-globin, PL2A and c-myc) and primer-probe system (CD24) [17][18][19]. CD24 expression was determined according to a previously described method [17].…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…CD24 expression was determined according to a previously described method [17]. c-myc and PL2A gene specific primers were designed and synthesized by TIB MOLBIOL (Berlin, Germany) [18,20]. The house-keeping gene β-globin expression was measured and used for normalization of the gene expression results.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14]. Prognostic prediction based on gene expression profiles has been attempted by two groups, but the ''prognostic gene lists'' have shown little or no overlap (13,15,16).…”
Section: Introductionmentioning
confidence: 99%